Youth Multi-Association Participation and Public Space: Evidence from the Chilean Case - Daniel Carmen (International Journal of Science and Society, 2023)
The objective of the article is to expose a set of reflections and empirical findings related to the phenomenon of youth associative participation and its relationship with the development of greater civility as a condition of democratic strengthening. Within this framework, a series of findings related to the phenomenon of "multi-adherence" is presented, establishing, in this way, its theoretical importance, its conceptualization, to advance in the exploration of its relationship with the development of civic behavior. In this way, it seeks to determine, first, if the multi-adherence phenomenon constitutes an instrument of social integration typical of the cultural model present in our societies; second, what kind of motivations encourage and/or discourage young people to participate in multiple ways; third, if an eventual multi-membership is a strategy of increasingly broad social and ideological experimentation; and, finally, what is the impact of a possible multi-membership on the civic life of young people and the consequences that it may have on public policiesThe objective of the article is to expose a set of reflections and empirical findings related to the phenomenon of youth associative participation and its relationship with the development of greater civility as a condition of democratic strengthening. Within this framework, a series of findings related to the phenomenon of "multi-adherence" is presented, establishing, in this way, its theoretical importance, its conceptualization, to advance in the exploration of its relationship with the development of civic behavior. In this way, it seeks to determine, first, if the multi-adherence phenomenon constitutes an instrument of social integration typical of the cultural model present in our societies; second, what kind of motivations encourage and/or discourage young people to participate in multiple ways; third, if an eventual multi-membership is a strategy of increasingly broad social and ideological experimentation; and, finally, what is the impact of a possible multi-membership on the civic life of young people and the consequences that it may have on public policies.